Effects of Reverberation on the Relationship between Compression Speed and Working Memory for Speech-in-Noise Perception - Reinhart, Paul (Ear Hear, 2019)
OBJECTIVES: Previous work has suggested that when listening in modulated noise, individuals benefit from different wide dynamic range compression (WDRC) speeds depending on their working memory ability. Reverberation reduces the modulation depth of signals and may impact the relationship between WDRC speed and working memory. The purpose of this study was to examine this relationship across a range of reverberant conditions. DESIGN: Twenty-eight older listeners with mild-to-moderate sensorineural hearing impairment were recruited in the current study. Individual working memory was measured using a reading span test. Sentences were combined with noise at two signal-to-noise ratios (2 and 5 dB SNR), and reverberation was simulated at a range of reverberation times (0.00, 0.75, 1.50, and 3.00 seconds). Speech intelligibility was measured in listeners when listening to the sentences processed with simulated fast-acting and slow-acting WDRC conditions. RESULTS: There was a significant relationship between WDRC speed and working memory with minimal or no reverberation. Consistent with previous research, this relationship was such that individuals with high working memory had higher speech intelligibility with fast-acting WDRC, and individuals with low working memory performed better with slow-acting WDRC. However, at longer reverberation times there was no relationship between WDRC speed and working memory. CONCLUSIONS: Consistent with previous studies, results suggest that there is an advantage of tailoring WDRC speed based on an individual’s working memory under anechoic conditions. However, the present results further suggest that there may not be such a benefit in reverberant listening environments due to reduction in signal modulation.